2011
DOI: 10.3109/02699206.2011.588371
|View full text |Cite
|
Sign up to set email alerts
|

Children's development of intonation during the first year of cochlear implant experience

Abstract: This article describes the longitudinal development of intonation in 18 deaf children who received cochlear implants (CIs) before the age of three years and 12 infants with typical development (TD) who served as controls. At the time their implants were activated, the children with CIs ranged in age from 9 to 36 months. Cross-group comparisons were made when the children had equivalent amounts of robust hearing experience but different chronological ages. This paper reports the results for the 6-month period e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Another child (HAGR) had a secondary disability related to motor speech. Snow and Ertmer (2012) reported that the pattern of intonation development in children with secondary disabilities was similar to that of other CI recipients.…”
Section: Children With Cismentioning
confidence: 76%
See 2 more Smart Citations
“…Another child (HAGR) had a secondary disability related to motor speech. Snow and Ertmer (2012) reported that the pattern of intonation development in children with secondary disabilities was similar to that of other CI recipients.…”
Section: Children With Cismentioning
confidence: 76%
“…Visual inspection of the first year of robust hearing shows little resemblance to the corresponding part of the graph for children with NH. This is due to a significant interaction between "age at activation" and amount of robust hearing experiencethe principal finding in the first year of the study (Snow & Ertmer, 2012). As a result of the interaction, the older children progressed more rapidly than the younger groups.…”
Section: Children With Cismentioning
confidence: 87%
See 1 more Smart Citation
“…Although fine structure information transmitted by CI devices is degraded, prosodic cues are not completely absent (Wilson and Dorman, 2008) and CI users can process auditory prosodic cues to some extent (e.g. Spitzer et al 2009;Meister et al, 2011;Snow and Ertmer, 2012;Segal et al, 2016). Training in this aspect of speech is therefore feasible and needs to be systematically included in rehabilitation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Intonational cues also seem to be processed by CI users to some extent. In a longitudinal study, Snow and Ertmer (2012) analyzed the accent range (i.e. the amount of F0 change used in falling or rising contours) during the spontaneous speech production of CI children.…”
Section: Introductionmentioning
confidence: 99%